Death and dollars : the role of gifts and bequests in America - Munnell, Alicia Haydock; Sunden, Annika E. (Washington, D.C. : Brookings Institution Press, 2003)
Annotation Despite the recent downturn in the stock market, the 1990s boom and the shift to defined contribution plans mean that more individuals will have significant wealth upon retirement. How they use that wealth will determine not only their own well-being, but also the living standards of their children, the resources available to philanthropies, and the level of investment capital in the economy. This volume explores the reasons why people save, how they decide to allocate their wealth once they retire, and how givers select their beneficiaries. It also assesses the extent to which the estate tax and annuitization of retirement wealth affects the amount and nature of wealth transfers. Finally, it looks at the impact of wealth transfersfirst on the amount of aggregate saving and capital accumulation, and then on the distribution of wealth among households. Several conclusions emerge. First, gifts and bequests are important; they may account for about half of total wealth in America. Second, rich people make most, of the wealth transfers. They are thoughtful about how much they pay in taxes and how they dispose of their wealth. They care about philanthropic causes and view their charitable contributions as more than a way to avoid paying estate taxes. Third, most nonrich people probably have some lexicographic preferences about the disposition of their wealth; they want to ensure they have adequate resources to take care of their own needs, and if money is left over, they would like it to go to their children. Fourth, little support has emerged for the pure altruistic model of bequests. Fifth, institutions matter. In the case of the rich, the estate tax probably reduces saving and increasesbequests to charity. In the case of the nonrich, the shift to defined contribution plans will at a minimum mean that they have more wealth in their hands when they die, and therefore they will leave larger accidental bequests.
Chapter 1. Introduction / Alicia H. Munnell -- Part One. The U.S. experience in perspective -- Chapter 2. A history of bequests in the United States / J. Bradford Delong -- Comments by Peter A. Diamond and Jonathan Skinner -- Chapter 3. The role of gift and estate transfers in the United States and in Europe / Pierre Pestieau -- Comment by Peter R. Orszag -- Part Two. How do people leave bequests? -- Chapter 4. Bequests: by accident or by design? / Michael D. Hurd -- Comments by Andrew B. Abel and Jonathan Gruber -- Chapter 5. Gifts and bequests: family or philanthropic organizations? / Paul G. Schervish and John J. Havens -- Comments by James Andreoni and Charles Clotfelter -- Chapter 6. Private transfers within the family: mothers, fathers, sons, and daughters / Donald Cox -- Comments by Theodore Bergstrom and Kathleen McGarry -- Part Three. Taxes, pension benefits, and wealth transfers -- Chapter 7. Tax consequences on wealth accumulation and transfers of the rich / Wojciech Kopczuk and Joel Slemrod -- Comments by Ray D. Madoff and James Poterba -- Chapter 8. The impact of defined contribution plans on bequests / Alicia Munnell, Annika Sundén, Mauricio Soto, and Catherine Taylor -- Comments by Amy Finkelstein and Olivia S. Mitchell -- Part Four. Wealth transfers and the economy -- Chapter 9. The impact of gifts and bequests on aggregate saving and capital accumulation / William G. Gale and Samara Potter -- Comments by Peter A. Diamond and Laurence J. Kotlikoff -- Chapter 10. The impact of gifts and bequests on the distribution of wealth / Edward N. Wolff -- Comments by John Laitner and John Karl Scholz.
Includes bibliographical references (pages 389-409) and index.
Print version record.
English.
JSTOR
Keywords: Inheritance and succession -- United States; Wealth -- United States; Charitable uses, trusts, and foundations -- United States; Charitable bequests -- United States; Successions et héritages -- États-Unis.; Richesse -- États-Unis.; Fondations (Droit) -- États-Unis.; Legs de charité -- États-Unis.; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Macroeconomics; BUSINESS & ECONOMICS -- Personal Finance -- General; Charitable bequests; Charitable uses, trusts, and foundations; Inheritance and succession; Wealth; United States